AAPE proliposomes for topical atopic dermatitis treatment. (December 2014) - Jahn, Alexander; Song, Chung Kil; Balakrishnan, Prabagar; Hong, Soon-Sun; Lee, Ju-Hee; Chung, Suk-Jae; Kim, Dae-Duk
Abstract Context: Anti-inflammatory effect of advanced adipose stem cell derived protein extract (AAPE) could be improved by minimising protein degradation. Objective: To develop a proliposomal formulation of AAPE for the treatment of topical atopic dermatitis. Materials and methods: Proliposomal powder was manufactured by evaporating a solution of soy phosphatidyl choline, AAPE and Poloxamer 407 in ethanol under vacuum on sorbitol powder. Characterisation of proliposomes (zeta potential, diameter, stability and flowability) as well as in vivo efficacy in a dermatitis mouse model was investigated. Results and discussion: Reconstitution of the proliposomal powder formed liposomes of 589 ± 3.6 nm diameter with zeta potential of −51.33 ± 0.36 mV. Protein stability was maintained up to 90 days at 25 °C as proliposomes. In vivo studies on atopic dermatitis mouse model showed a significant reduction in IgE levels after topical AAPE proliposome treatment. Conclusion: AAPE proliposomes maintained protein stability and showed promising results for atopic dermatitis treatment.